Metasurface-enabled electromagnetic illusion with generic algorithm - Zhu, Rongrong; Chen, Tianhang; Wang, Kai; Wu, Hao; Lu, Huan (Frontiers in Materials, 2023)
Electromagnetic cloak or illusion, which can interfere with device detection and provide superior self-protection capabilities for animals or humans, has received much attention. The proposal of transformation optics provides a generalized strategy for realizing electromagnetic illusion. However, the complex parameter composition causes a substantial computational cost, which is not conducive to practical applications. To overcome these challenges, we report an intelligent illusory metasurface optimized by a genetic algorithm, which not only presents predefined illusory effects but also reduces the parameter space in physics. By designing a high-performance tunable metasurface, a high-fidelity inverse design is performed in simulation. Near-field and far field results show that the metasurface can generate virtual targets in different scenarios and realize electromagnetic illusion. This work is helpful in facilitating the practical application of electromagnetic illusion strategies.